2 - No African Futures without the Liberation of Women: A Decolonial Feminist Perspective - Nkenkana, Akhona (Africa Development, 2021)
Coloniality of gender speaks to the perennial question of the liberation of women from various forms of oppression. The ‘modern’ world system and its global order have remained fundamentally patriarchal. This implies that any initiative aimed at creating African futures has to address the fundamental question of the liberation of women. Liberation of women does not speak to the incorporation of women within the patriarchal system. The first step, as Thomas Sankara said in his 1987 speech, is to understand how the patriarchal system functions, to grasp its real nature in all its subtlety, in order to work out a line of action that can lead to women’s genuine emancipation. Decolonising gender therefore becomes a necessary task so that answers to what should be done are formulated from the perspective of asking correct questions. Decolonising gender is to enact a critique of racialized, colonial, and capitalist heterosexualist gender oppression as a lived transformation of the social (Lugones 2010). As such, decolonizing gender places the scholar in the midst of people in a historical, peopled, subjective/intersubjective understanding of the oppressing-resisting relation at the intersection of complex systems of oppression. To a significant extent, it has to be in accord with the subjectivities and intersubjectivities that construct and in part are constructed by the situation. This article deploys decolonial feminist ideas of Thomas Sankara, amomg others, to push forward the frontiers of the struggle for the liberation of women as a constitutive part of initiatives of creating African futures. Its central argument is that women’s liberation struggle should not be reduced to efforts of incorporation of women within the patriarchal, colonial and imperial modern system/s women seek to reject. Making use of Maria Lugones’ theoretical framework, we should be able to understand that the instrumentality of the colonial/modern gender system is subjecting both men and women of colour in all domains of existence and therefore allows us to reveal that the gender transformation discourse is not just a women’s emancipation discourse but rather efforts of both men and women to overcome the colonial global structure that is subjectifying in different ways. The change of the system and its structures, which are essentially patriarchal, is the main mechanism that will bring about possible equal futures for women in Africa, as case studies of Rwanda and South Africa show in the article.